Caricature as a creative work for its creator and viewer - Zača, Evija (Creativity Studies, 2012)
Nowadays we can witness a tendency where the visual replaces the verbal. Humour experiences the same: its visual expression – caricature – is a visual metaphor that already has taken its remarkable place in the field of humour. Caricatures have become a distorting mirror that show deformed but still fairly presented reality. Humour is important part of our everyday life’s communication and it covers many spheres of people’s life, even including marketing, politics, work relationships, etc. That is why caricatures became a remarkable tool, for example, in political contentions. This article will show what it takes to create this distorting mirror from one side and to see a reflection in it and accept it from the other side. Karikatūra kaip kūrybinis darbas jo kūrėjui ir suvokėjui Santrauka. Nūdien esame liudininkais tendencijos, kai vizualumas išstumia verbalumą. Ši tendencija neaplenkia ir humoro: karikatūra, kaip jo vizualioji išraiška, yra toji vizualinė metafora, kuri užėmė svarbią vietą humoristikoje. Karikatūros tapo iškreipiančiu veidrodžiu, rodančiu deformuotą, bet dar pakankamai reprezentatyvią realybę. Humoras yra svarbi mūsų kasdienio gyvenimo komunikacijos dalis, aprėpianti daugelį jo sričių – rinką, politiką, darbo santykius ir t. t. Štai kodėl karikatūros tapo svarbiu įrankiu, pavyzdžiui, politiniuose ginčuose. Šiame straipsnyje parodoma, kaip, viena vertus, sukuriamas šis iškreipiantis veidrodis ir, kita vertus, koks atvaizdas jame regimas. Reikšminiai žodžiai: karikatūra, kūrybingumas, humoras, ironija, žinojimas.